(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the effectiveness of the wall slide exercise for the upper limb in improving scapular upward rotation in patients with limited shoulder abduction. Subjects and methods: A prospective pre-post intervention study was conducted on 40 patients aged ≥ 18 years at the Rehabilitation Center of Bach Mai Hospital from February 2024 to February 2025. All participants presented with limited scapular upward rotation during maximal shoulder abduction. Scapular rotation angle was measured using a smartphone-based goniometer application before and after a 4-week wall slide exercise program. Results: The mean scapular upward rotation angle increased significantly from 35.23 ± 6.62 degrees at baseline to 48.17 ± 4.59 degrees after 4 weeks, with an average improvement of 12.94 ± 4.73 degrees. No significant adverse events were reported. Conclusion: The upper limb wall slide exercise is effective in improving scapular kinematics and reducing pain in patients with shoulder movement limitations. This exercise is simple, safe, and highly applicable in rehabilitation practice.